AIMS65 score in Kuantan - Mohd Firdaus, Mohd Al-Baqlish; Hasmoni, Mohamed Hadzri; Jaafar, Khairul Azhar (IIUM Press, International Islamic University Malaysia, 2017)
Current guidelines on the management of acute upper gastrointestinal bleeding (AUGIB) suggested an early risk stratification of patients to predict prognosis of the disease. However, the current available scores are complex and have not been widely used in clinical practice. AIMS65 score is a simple score that can be used to risk stratify patients with AUGIB.